Socialização docente e experiências pré-profissionais - Moura Clates, Daniela de (2019)
This descriptive study aims to analyse the different experiences accumulated over the graduation period and their impact on the process of initiation into schooling. Biographical accounts of six graduates of a Bachelor of Physical Education of Santa Maria University were used, with a maximum of three years of teaching. The study shows that young teachers create professional habitus on campus. In this space, unequal relationships take place caused by recognition dispute. Thus, newcomers will have to adapt to those situations already imposed or seek strategies to change that reality. In some situations, they can make use of the experiences and learnings from their student days; this is often made possible by their participation in different formative spaces parallel to the curriculum (teaching / research / extension projects, student movement).